Risk Factors for Low Academic Performance and Social Inequality in Peru according to PISA 2012 - Muelle, Luis (2016)
This study applies a multilevel logistic model to the results obtained by Peruvian students in the PISA2012 survey and analyzes the factors associated with risk for low academic performance in level 2 competencies, using as a baseline mathematics, reading, and science skills tests.The students’ socio-economic background and the social composition of their schools stand out as the factors that most affect at-risk students. Parental occupation, family structure, attendance in pre-primary education, grade repetition, the student’s native language, and delay in schooling are factors that affect the probability of risk. At the school level, it is noteworthy that traditional factors such as school size, urban/rural location, and public/private management were not found to be significant.